(untitled) (Research, Society and Development, 2022)
Introduction: The teaching work is essential for society, but of high demand and low valuation, which can interfere with the health of teachers. Objective: to evaluate the influence of teaching work on the style, quality of life (QL), and level of physical activity (PA) of teachers. Methods: Cross-sectional study evaluated elementary school teachers from public schools. Self-reported instruments were used by the participants on the professional profile, body mass, height, and the body mass index (BMI) was calculated. was assessed by the Quality of Life Questionnaire - SF-36, and the PA level by the International Physical Activity Questionnaire - IPAQ. Results: 93 female teachers participated, with a mean age of (43.5 ± 7.8) years, BMI (26.9 ± 4.8), with a weekly workload of (40.4 ± 13.4) hours and service time of (16.5 ± 7.9) years. Regarding PEVI, nutrition (1.57 ± 0.8), PA (0.94 ± 0.9), and stress control (1.68 ± 0.9. Regarding QoL, they are close to the minimum reference values 73.2% of the teachers were classified by the IPAQ as irregularly active or sedentary. No correlation was found between the variables. There was an association p(0.01) between PA, teaching time and PEVI. Conclusion: It was possible to conclude that although teachers were considered to have a good QoL, most were classified as overweight, a lifestyle below a healthy level and insufficiently active Institutional strategies should be implemented to prevent teachers from falling ill.